Monitoring the Lithium Concentration across the Thickness of Silicon-Graphite Electrodes during the First (De-)Lithiation. Issue 8 (1st January 2019) - Wetjen, Morten; Trunk, Markus; Werner, Lukas; Gasteiger, Hubert A.; Gernhäuser, Roman; Gilles, Ralph; Märkisch, Bastian; Révay, Zsolt
Abstract : Progressing from graphite to silicon-based anodes for lithium-ion batteries increases the importance of a depth-resolved understanding of the reversible and irreversible processes across the thickness of the anode electrode. Considerable changes in electrode volume and mass loading upon (de–)lithiation make silicon electrodes more susceptible to continuous side reactions and to the isolation of active material particles, leading to non-uniform and accelerated electrode degradation. Here, we investigate the evolution of lithium concentration profiles across the thickness of porous silicon-graphite (SiG) electrodes (∼20 μm thickness, ∼1.7 mAh cm −2 ) with 35 wt% silicon nanoparticles during the first (de–)lithiation cycle. Using ex situ neutron depth profiling (NDP), we monitor depth- and quantity-resolved (i) the solid-electrolyte-interphase (SEI) formation, (ii) the (de–)lithiation of the active materials, as well as (iii) the changes in the total lithium content as a function of the state-of-charge (SOC) and depth-of-discharge (DOD). The results provide depth–resolved information about reversible and irreversible processes occurring during the formation of SiG electrodes, and thus offer insight into the formation process of silicon-based electrodes.